2022
DOI: 10.1080/2162402x.2022.2055703
|View full text |Cite
|
Sign up to set email alerts
|

Superior antitumor immunotherapy efficacy of kynureninase modified CAR-T cells through targeting kynurenine metabolism

Abstract: Accumulated oncometabolites in the tumor microenvironment (TME) suppresses the metabolism, expansion, and function of T cells. Immunosuppressive TME also impeded Chimeric Antigen Receptor (CAR)-T cells mediated cytotoxicity since CAR-T cells had to adapt the in vivo metabolic characteristics with high levels of oncometabolites. We screened oncometabolites for the inhibition of glucose uptake in CD8 + T cells and found Kynurenine (Kyn) showed the strongest inhibiting effect on glucose uptake. In vitro experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Strategies that incorporate other heterologous response elements (e.g., dioxin responsive element or hypoxic responsive element) that allow for response to other mechanisms of immune suppression tumors may also be promising routes to expand the function and utility of these synthetic promoters. [55][56][57] In sum, we engineered effective ADOactivated promoters with high induction strengths that are activated in response to tumoral environmental conditions, as well as put forward considerations for testing ADO-mediated cellular responses in vitro with FBS.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies that incorporate other heterologous response elements (e.g., dioxin responsive element or hypoxic responsive element) that allow for response to other mechanisms of immune suppression tumors may also be promising routes to expand the function and utility of these synthetic promoters. [55][56][57] In sum, we engineered effective ADOactivated promoters with high induction strengths that are activated in response to tumoral environmental conditions, as well as put forward considerations for testing ADO-mediated cellular responses in vitro with FBS.…”
Section: Discussionmentioning
confidence: 99%
“…KYNU is widely expressed in nearly all organs of the body, with particularly elevated levels observed in the liver, urinary bladder, and appendix. 50 KYNU is involved in various inflammatory skin diseases, [51][52][53][54][55] cardiovascular diseases, 56 inflammatory bowel disease, 57,58 and several types of cancers, [59][60][61][62][63] exerting its effects through diverse pathways. While previous studies have indicated abnormalities in tryptophan metabolism within HS lesions, 18 there is currently a scarcity of research confirming the distinctive expression pattern of KYNU specifically in HS.…”
Section: Discussionmentioning
confidence: 99%
“…Kynurenine (Kyn) is an oncometabolite which exists in various hematopoietic malignancies, such as lymphoma and leukemia, and the enzyme kynurenine catalyzes the degradation of Kyn. Thus, the anti-CD19 CAR-T cells were genetically modified with the enzyme kynurenine gene, and they exhibited the improved antitumor activity against Nalm6-GL cells in the immunosuppressive tumor microenvironment with high Kyn (269). Interestingly, some target antigens are co-expressed on immunosuppressive cells in tumor microenvironment, so targeting these antigens can simultaneously eliminate malignant cells and immunosuppressive cells.…”
Section: Overcoming Immunosuppressive Microenvironmentmentioning
confidence: 99%